Stratigraphic evidence for seven meters of dextral slip on the San Andreas fault during the 1857 earthquake in the Carrizo Plain - Sieh, Kerry (2013)
The smallest geomorphic offsets along a 35 km section of the San Andreas fault in the Carrizo Plain vary from 7 to 10 m. Our three-dimensional excavation of alluvial deposits a few km southeast of Wallace Creek confirms that at least 6.6 to 6.9 m of dextral slip occurred there during the latest large earthquake, in 1857. Dates on detrital charcoal suggest that the last event prior to the 1857 earthquake occurred before a date within the range A.D. 1305 to 1623. The 3-m range in smallest offsets along this portion of the fault may reflect either a 3-m variation in slip along the San Andreas in 1857, or 2 to 3 m of slip during an event prior to 1857. Observations made after the recent Landers earthquake are compatible with the hypothesis of large, local variations in slip during a single earthquake, but do not explain the cause of such variations. Off-fault dextral rotations would be one plausible explanation. However, paleoseismic data in the Carrizo Plain are too sparse to allow rejection of the alternative hypothesis that slip in the event prior to 1857 was only 2 to 3 m, an amount of slip which would be several times too small to fit a time-predictable model.